Optimization of Production Process with Re-Planning of Logistic Facility Layout Using Systematic Layout Planning Method (Case Study in the Lubricant Manufacturing Industry) - Teddy Wahyudi; Humiras Hardi Purba (Jurnal Media Teknik dan Sistem Industri, 2026)
This research investigates the optimization of production processes through the redesign of logistics facility layouts. The research was conducted in a lubricant manufacturing industry that commands approximately 30% of Indonesia's lubricant market share. The factory has experienced bottlenecks in material and finished goods movement due to a threefold increase in production capacity, from 50-67 million liters to 176 million liters per year. This condition has led to wasted time and costs, necessitating improvements in material handling. This study aims to quantitatively measure and analyze the impact of facility layout redesign using the Systematic Layout Planning (SLP) method and compare it with block plan software simulation. The research methodology involves data collection, material flow analysis, and proposed layout design. Following the implementation of the proposed SLP layout, there was an efficiency increase of 15.56% in rectilinear distance (reducing to 691.4 m), 12.46% in OMH (reducing to IDR 2,451,421) and 12.31% in moment (reducing to 15744). Meanwhile, the proposed Bloc plan layout demonstrated more significant efficiencies: 51.33% for rectilinear distance (reducing to 398.5 m), 28.17% for OMH (reducing to IDR 2,011,558), and 28.95% for moment (reducing to 12756). Although Bloc plan offers higher efficiency, the SLP method is suggested in this study given the field conditions and available space.